Healthcare resource utilization in myeloproliferative neoplasms: a population-based study from Ontario, Canada. Issue 8 (2nd July 2020) - Bankar, Aniket; Zhao, Haoyu; Iqbal, Javaid; Coxford, Ruth; Cheung, Matthew C.; Mozessohn, Lee; Earle, Craig C.; Gupta, Vikas
Abstract: Health resource utilization (HRU) and associated factors of high cost are not well understood in myeloproliferative neoplasms (MPNs). In this population-based, retrospective matched-cohort study, we used administrative health databases of Ontario, Canada to measure treatment costs and HRU for patients with MPN from 2004 to 2016 and compared them to matched controls. In 7130 patients with MPN [essential thrombocythemia (ET) = 3481; polycythemia vera (PV) = 2618; myelofibrosis (MF) = 1031], the mean annualized treatment costs were 16, 646 for ET (controls, 7070); 16, 360 for PV (controls, 7293); and 25, 863 for MF (controls, 7386). Out of the total costs, the largest expenditure was on acute hospital care (ET: 57%, PV: 57%, MF: 66%). Older age (≥65), male gender, patients not seen by a specialist, and greater comorbidity burden were independent predictors of higher costs ( p < 0.05). In addition, history of venous thrombosis in patients with ET and PV was associated with significantly higher treatment costs ( p < 0.05).